Scenarios III : Stroszek : Nosferatu, phantom of the night : Where the green ants dream : Cobra verde - Herzog, Werner, 1942- (University of Minnesota Press, 2019)
"Scenarios III is the third volume collecting Herzog's earliest film scripts. It collects 4 scenarios (none of them have ever been in English until now): Stroszek; Nosferatu, Phantom of the Night; Where the Green Ants Dream; Cobra Verde"--